Neurodevelopment Outcome among Preterm Infants Admitted in Neonatal Intensive Care Unit - Jahan, Mosammad Alpana; Shuma, Afroza Islam; Sultana, Rabeya; Rumman; Jahan, Ismat; Shabuj, Mohammad Kamrul Hassan; Dey, Sanjoy Kumer; M A Mannan; Shahidullah, Mohammod (Journal of Dhaka Medical College, 2024)
Introduction: With increasing the survival rates of premature babies, the management of long term complications, especially neurodevelopmental disorder is becoming an important issue for a better life. Aims: To assess the factors associated with adverse neurodevelopment outcome among preterm infants admitted in Neonatal Intensive Care Unit (NICU). Methods and Material: This prospective cohort study was conducted in Department of Neonatology, BSMMU, Dhaka, Bangladesh. Premature infants (<34 weeks) discharged from the NICU were enrolled and followed up for neurodevelopmental assessment at 6 months of age. Prenatal, perinatal, and postnatal features of the babies were recorded. The Bayley-III scale was used to assess the composite scores. Continuous variables were analyzed using an independent t-test and categorical variables with chi-square test. Logistic regression analysis was performed to find out the relationship of risk factors with neurodevelopmental scores. Results: A total 47 patients were analysed at 6 months of age using Bayley scale III. Mean birth weight and gestational age was 1595.11 ± 377.17g and 32.43 ± 1.48 weeks respectively. Mean cognitive, motor and language score were 80.79±14.51, 82.87±14.53 and 82.98±13.72 respectively. Despite the fact that all mean scores were normal, 27.7% of infants in cognition, 23.4% in motor, and 31.9% in language had a BSID-III value < 70. Variables like gestational age < 30 weeks, birth weight <1500 grams, and convulsion have been linked to poor neurodevelopmental outcomes. However, regression analysis revealed none of them were significant. Conclusions: In our study, at six months of age, the cognitive, language, and motor scores of preterm newborns (less than 34 weeks of gestation) were within normal limits. Of the newborns, we observed that 27.7% had cognitive delay and 31.9% experienced language delay. J Dhaka Med Coll. 2022; 31(2) : 251-257